La imaginación, una vía para pensar la educación de las nuevas generaciones (2018)
Today display a different picture is the last thing young, swallowed up in a vertiginous and voracious world, they assume their present and future are in charge, the transformation of the picture begins today, imagining a different reality, a landscape more colorful and affable, teachers can be detonators for new generations imagine different horizons, permeated of dialogue, respect, freedom, understanding and multiplicity.